Association of pre-pregnancy body mass index and gestational weight gain with continued breastfeeding until 6 months postpartum in Japanese women: the Japan Environment and Children’s Study - Hidekuni Inadera; Kenta Matsumura; Takashi Yoda; Takashi Nakano; Haruka Kasamatsu; Kanako Shimada; Akiko Tsuchida; the Japan Environment and Children’s Study Group (BMC Pregnancy and Childbirth)
Abstract Background The relationship of pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) with continued breastfeeding (BF) in Japanese women remains unclear. To evaluate different maternal pre-pregnancy BMI and GWG categories according to the initial BMI, we conducted an analysis of continued BF until 6 months postpartum in a large Japanese cohort. Methods This study used data from the Japan Environment and Children’s Study, which included approximately 100,000 pregnant women. Pre-pregnancy BMI (kg/m2) was categorized as underweight (BMI < 18.5), normal weight (BMI 18.5–24.9), and overweight (BMI 25.0–29.9). GWG was categorized as insufficient, optimal, and excessive based on the 2021 criteria from the Japanese Society of Obstetrics and Gynecology. Continued BF for the first 6 months postpartum was categorized into 3 patterns: exclusive BF (EBF), non-EBF type-I (6 months of BF with formula), and non-EBF type-II (< 6 months of BF). Logistic regression analysis was conducted to evaluate the association of pre-pregnancy BMI and GWG with continued BF. Normal BMI and optimal GWG and EBF were used as reference values while controlling for covariates. Results Of 82,129 women with singleton pregnancies, BMI was categorized as underweight in 16.6%, normal weight in 75.3%, and overweight in 8.1%. The rate of EBF in these groups was 37.1% for underweight, 37.2% for normal weight, and 26.8% for overweight. In underweight women, both insufficient and excessive GWG were associated with higher rates of non-EBF type-II. In normal-weight women, insufficient and excessive GWG were associated with higher rates of non-EBF type-II. Overweight women showed higher rates of non-EBF type-I and type-II, irrespective of GWG. Conclusions Our results indicate that the effects of GWG on continued BF were associated with pre-pregnancy BMI. Adequate GWG should be recommended to underweight and normal-weight women to promote BF. Efforts toward the prevention of overweight prior to pregnancy should be encouraged to enhance BF.